Reconstruction of Orthographic Mosaics from Perspective X-Ray Images - Fotouhi, Javad; Liu, Xingtong; Armand, Mehran; Navab, Nassir; Unberath, Mathias (IEEE Transactions on Medical Imaging, 2021)
Image stitching is a prominent challenge in medical imaging, where the limited field-of-view captured by single images prohibits holistic analysis of patient anatomy. The barrier that prevents straight-forward mosaicing of 2D images is depth mismatch due to parallax. In this work, we leverage the Fourier slice theorem to aggregate information from multiple transmission images in parallax-free domains using fundamental principles of X-ray image formation. The details of the stitched image are subsequently restored using a novel deep learning strategy that exploits similarity measures designed around frequency, as well as dense and sparse spatial image content. Our work provides evidence that reconstruction of orthographic mosaics is possible with realistic motions of the C-arm involving both translation and rotation. We also show that these orthographic mosaics enable metric measurements of clinically relevant quantities directly on the 2D image plane.
CRIS-Team Scopus Importer:2023-03-08
Keywords: ConvNet; GAN; image reconstruction; landmark; parallax; stitching; X-ray